Using stock returns to identify government spending shocks - Jonas D.M. Fisher; Ryan Peters (Federal Reserve Bank of Chicago, 2009)
This paper explores a new approach to identifying government spending shocks which avoids many of the shortcomings of existing approaches. The new approach is to identify government spending shocks with statistical innovations to the accumulated excess returns of large US military contractors. This strategy is used to estimate the dynamic responses of output, hours, consumption and real wages to a government spending shock. We find that positive government spending shocks are associated with increases in output, hours, and consumption. Real wages initially decline after a government spending shock and then rise after a year. We estimate the government spending multiplier associated with increases in military spending to be about 0.6 over a horizon of 5 years.
Keywords: E0; E30; E60; 330; government spending shocks; fiscal policy; stock returns